The Invention of Neo-Socialism: The Dynamics of Schism and Doctrinal Distinction in the French Socialist Party. (July 2019) - Desan, Mathieu Hikaru
Abstract: What is the relationship between schism and political identity? Existing scholarship has tended to focus on the determinants of schism while treating the ideational basis on which schisms are made as largely fixed. In this paper, I develop a new interpretation of the 1933 "neo-socialist schism" within the French Socialist Party to highlight how new political identities can be constituted in and through the process of schism itself. The 1933 schism is often understood as the convergence of a doctrinal revision called "neo-socialism" and a separate tactical challenge to the party's parliamentary practice. But a careful reading of the factional conflict within the party reveals that it was the preceding tactical debate over ministerial participation that was transformed over time into a debate over socialist doctrine. This distinction between "tactics" and "doctrine" performatively defined the limits of acceptable party discourse, and as such was both a weapon and a stake in the factional conflict. I trace the evolution of this conflict and show that, so long as the minority faction was weak, the issue of participation was widely considered "tactical" and thus safe for discussion. But when minority strength grew, the majority sought to redefine the conflict as doctrinal to delegitimate the challengers. Finally, only when a schism appeared inevitable did the challengers themselves adopt the label of "neo-socialism." Neo-socialism was thus not a pre-constituted political heresy driving the schismatic process, but the contingent and emergent outcome of this very process.